The Influence of Emotional Intelligence, Adaptation, and Homesickness toward Stress Level - Meickel Peterson; Liswandi - (Management and Leadership Study Programme, 2019)
As freshmen, first semester of university life can be really challenging, being away from family and adapt to completely new environment. However if student can prevent stress, transition can be so much easier. The purpose of this study is to examine The Influence of Emotional Intelligence, Adaptation, and Homesickness toward the Stress Level of President University freshmen. This is a descriptive study using a quantitative approach. For the data collection this research used questionnaire. The samples collected in this study consisted of 113 freshmen. The result of this study showed that Emotional Intelligence has a negative significant influence toward Stress Level, Adaptation also has a negative significant influence toward Stress Level, and Homesickness has a positive significant influence toward Stress Level. This study suggested that by improving the Emotional Intelligence of a student, it will help adaptation process of freshmen, and reduce homesickness, President University student stress level can decrease significantly which will lead to boost of performance in academic and social.